2011
DOI: 10.5194/hess-15-437-2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rainfall retrievals from SEVIRI reflectances over West Africa using TRMM-PR and CMORPH

Abstract: Abstract. This paper describes the evaluation of the KNMI Cloud Physical Properties -Precipitation Properties (CPP-PP) algorithm over West Africa. The algorithm combines condensed water path (CWP), cloud phase (CPH), cloud particle effective radius (r e ), and cloud-top temperature (CTT) retrievals from visible, near-infrared and thermal infrared observations of the Spinning Enhanced Visible and Infrared Imager (SEVIRI) onboard the Meteosat Second Generation (MSG) satellites to estimate rain occurrence frequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Although model simulations, for example, European Centre for Medium-Range Weather Forecasts (ECMWF; Persson 2001) and Modern-Era Retrospective Analysis for Research and Application (MERRA;Rienecker et al 2011), have solved the spatial issue of precipitation data, their accuracy is not reliable (Anagnostopoulos et al 2010). On the other hand, satellite observations provide a unique opportunity to estimate (near) real-time precipitation globally with promising accuracy (Wolters et al 2011) that would be beneficial, especially for areas like Iran, where ground-based observations are scarce (Javanmard et al 2010). Therefore, estimating precipitation from remote sensing observations has become one of the main approaches to measuring precipitation in the last decades (Tan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although model simulations, for example, European Centre for Medium-Range Weather Forecasts (ECMWF; Persson 2001) and Modern-Era Retrospective Analysis for Research and Application (MERRA;Rienecker et al 2011), have solved the spatial issue of precipitation data, their accuracy is not reliable (Anagnostopoulos et al 2010). On the other hand, satellite observations provide a unique opportunity to estimate (near) real-time precipitation globally with promising accuracy (Wolters et al 2011) that would be beneficial, especially for areas like Iran, where ground-based observations are scarce (Javanmard et al 2010). Therefore, estimating precipitation from remote sensing observations has become one of the main approaches to measuring precipitation in the last decades (Tan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The ensemble of ALMIP-1 models revealed that total annual ET corresponds to 77% of the total annual precipitation in West Africa and 85% in the Sahel [21]. The annual precipitation cycle is highly subject to the West African monsoon [22]. Overall, the average precipitation rates increase southwards.…”
Section: Introductionmentioning
confidence: 99%
“…A number of validation efforts are underway worldwide to quantify the estimation errors, such as, the efforts of the International Precipitation Working Group (IPWG) covering Australia, Northern Europe, and North and South America [ Kidd et al ., ]. Validation studies in Africa are typically concerned with large‐scale and long‐term averages and therefore do not provide estimation error information at the native resolution of the satellite rainfall products useful for hydrological applications [e.g., Hirpa et al ., ; Yin and Gruber , ; Beighley et al ., ; Dinku et al ., ; Romilly and Gebremichael , ; Wolters et al ., ; Xue et al ., ; Adjei et al ., ; Habib et al ., ; Liechti et al ., ; Thiemig et al ., ; Novella and Thiaw , ]. The main challenge is that Africa has a very sparse rain gauge network, and the vast majority of the continent has no ground‐based weather radar.…”
Section: Introductionmentioning
confidence: 99%